Safeguarding social security for future generations leaving a legacy in an aging society - Achenbaum, W. Andrew (Routledge Taylor & Francis Group, 2023)
This book offers a unique multi-generational approach to saving Social Security. Public programs have adapted to societal aging, but fears overwhelm hopes for Social Security's future prospects. Conservatives want to privatize operations that liberals seek to expand. Younger workers are happy that Social Security protects their elders, but most do not expect benefits when needed. Achenbaum reframes conflicting perspectives and offers new models of respectful transgenerational dialogue that can mobilize pragmatic reforms. Designed for use in gerontology, social work, and public-policy courses, Safeguarding Social Security for Future Generations offers measured hope for leaving a legacy that safeguards the common good"--